2001
DOI: 10.1007/s00330-001-1198-9
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Ottawa knee rules in an emergency teaching centre

Abstract: Our objective was to determine the value of the Ottawa knee rules when applied by users with different levels of clinical training. We used a prospective patient survey by the medical students and surgery residents of a European university trauma centre. The study group consisted of 261 eligible patients who presented with acute knee trauma during a 6-month period. Radiography or follow-up was obtained for each patient. Data were separately analysed according to the degree of qualification of the initial exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(7 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…In the present study, OKR proved to be as specific as in most other studies 9 10 18 20. Two studies 5 19 reported lower levels of specificity (27% and 31.6% respectively), and only one study1 reported higher levels (52%). It should be mentioned that the lower confidence limit of the sensitivity in the present study is well below the critical value for cost-effectiveness, as calculated by Nichol and coworkers 21…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…In the present study, OKR proved to be as specific as in most other studies 9 10 18 20. Two studies 5 19 reported lower levels of specificity (27% and 31.6% respectively), and only one study1 reported higher levels (52%). It should be mentioned that the lower confidence limit of the sensitivity in the present study is well below the critical value for cost-effectiveness, as calculated by Nichol and coworkers 21…”
Section: Discussionsupporting
confidence: 51%
“…Most previous studies1 5 9 10 18 19 have reported sensitivities approaching 100%. Only one previous study20 reported a sensitivity of 84.6%, which is lower than that found in this study.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies have examined the use of several knee rules. 11,[13][14][15][16][17][18][19][20] In the study by Seaberg et al, 13 a comparison between the Ottawa Knee Rules and the Pittsburgh rules was made. A total of 934 patients were enrolled and ranged in age from 6 to 96 years.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 3907 adults, 100% sensitivity was achieved in detecting 59 fractures with a potential 26% reduction in radiographs (Stiell et al, 1997). The Ottawa knee rules remain highly sensitive when applied by medical personnel with different levels of quali®cation, such as encountered in a teaching setting (Emparanza and Aginaga, 2001;Ketelslegers et al, 2002). However, they would require modi®cation to accommodate the differences between paediatric and adult patients in order to improve the sensitivity of the rule while maintaining its speci®city, before being applied routinely in clinical paediatric practice (Khine et al, 2001).…”
Section: Investigationmentioning
confidence: 99%